AB0757 EULAR/ACR diagnostic and classification criteria of systemic vasculitis (DCVAS) study update. (23rd January 2014) - Robson, J.; Watts, R.; Grayson, P.; Suppiah, R.; Merkel, P.; Craven, A.; Luqmani, R.
Abstract : Background: Patients with vasculitis typically present with non-specific features, such as fever, fatigue and myalgia all of which are also common among different diseases. One of the aims of this study is to develop and validate diagnostic criteria for the primary systemic vasculitides (granulomatosis with polyangiitis [Wegeners], microscopic polyangiitis, Churg Strauss syndrome, polyarteritis nodosa, giant cell arteritis and Takayasu arteritis). We also aim to update the current 1990 ACR classification criteria, which has not been updated since the introduction of diagnostic tests such as anti-neutrophil cytoplasm antibody (ANCA). Objectives: Develop and validate diagnostic and classification criteria for the systemic vasculitides. Methods: Diagnostic criteria will be derived by comparing presenting features of patients with one type of vasculitis with vasculitis mimics to determine the discriminating features between the two groups. Classification criteria will be determined by comparing presenting features of patients with one type of vasculitis with those of patients with different types. Reference diagnoses will be determined using data-driven cluster analysis and compared with expert panel consensus. The recruitment target is 2000 patients with a diagnosis of vasculitis and 1500 patients with diseases which mimic vasculitis. Results: By January 2012, a total of 658 patients had been recruited by 33 sites from 18 countries. The graph in figure 1 displays the numbers of patients recruited with each baseline diagnosis. Conclusions: The DCVAS study is using a collaborative, international approach to identify large numbers of patients with vasculitis and mimic conditions, in order to develop new classification and diagnostic classification criteria. Disclosure of Interest: None Declared